Studi Komparatif: Tingkat Sport Anxiety dalam Pembelajaran PJOK Berdasarkan Perspektif Gender Siswa Kelas 7 SMP Negeri 1 Masbagik - Rizwan Septiadin; Rina Nopiana (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Physical Education (PJOK) in schools plays a vital role in students' physical and psychological development, yet execution in practical exams often triggers performance anxiety. This study aims to analyze the differences in sport anxiety levels in Physical Education (PJOK) learning based on a gender perspective among seventh-grade students at SMP Negeri 1 Masbagik. This quantitative study utilized a causal-comparative (ex post facto) approach. The research sample consisted of 64 seventh-grade students selected using a random sampling technique. Sport anxiety data were collected through a questionnaire adapted from the Sport Anxiety Scale-2 (SAS-2), covering the dimensions of somatic anxiety, worry, and concentration disruption. Data were analyzed using descriptive statistics and the Independent Samples t-Test. Descriptive analysis indicated that the mean sport anxiety score for female students (34.19 ± 7.01) was higher than that for male students (31.31 ± 6.44). However, the t-test results proved that this difference was not statistically significant (t (62) = -1.709; p = 0.092 > 0.05). The obtained effect size of 0.43 (Cohen's d) fell into the small-to-medium category. This study concludes that gender is not a dominant factor differentiating students' sport anxiety levels in PJOK learning. Practically, PJOK teachers are encouraged to implement inclusive teaching strategies that focus on creating a supportive learning environment to reduce anxiety for all students regardless of gender.